Multi-Level Mitigation Against Abrasion at The Ring-1 Local Transmigrant Area of Bugel Village, Kulon Progo, Indonesia - Oriza Herastuti, Karina; Maisarah, Siti Masyithoh; Srianti, Novi Mega; Prih Nurlia, Nadya Devista; Marsida, Feby Aulia; Anggara, Vivi Silvia; Ruslanjari, Dina (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
Abrasion has impacted the Local Transmigrant Area of Bugel Village, KulonProgo, Yogyakarta, Indonesia. In the past 5 years, abrasion has diminished distance between houses and shoreline up to 45,66 – 80,66 meters. Z-Score based quantitative method is implemented for vulnerability study, whilst descriptive qualitative based on cross tabulation is used for SWOT analysis. As a majority, 29% among 55 houses are classified as highly-vulnerable against abrasion. SWOT analysis indicated that in order to have a proper multi-level mitigation scenario, it is paramount tomitigate among each household by doing adaptation scenario amid rainy season, gainingnon-agricultural skills, createsavings, and involved in local communities. Also, within community level, it is considerably important to plant and make more coastal vegetations especially cemaraudang(Casuarina equisetifolia)along with limestone as protection. Lastly, within collective level, mitigation might be done by make cooperation with academists and local government for a better implementation of 6M which consists of (1) measurement of coastal abrasion, (2) mechanism of coastal abrasion understanding, (3) modelling for predictions, (4) monetary aspects (Cost Benefit Analysis/CBA), (5) measures’ implementation, as well as (6) monitor and evaluate the progress of abrasion.